The Influence of 3D Interactive Animation Media with a Project-Based Learning Approach on IPAS Learning Outcomes - Yeyen Sunarli; Erma Yulaini; Budi Utomo (Global Education Journal, 2026)
Natural and Social Sciences (IPAS) is one of the important subjects in elementary schools that aims to form students to have an understanding of natural and social phenomena, and to be able to think critically about the surrounding environment. This study aims to determine the effect of the use of 3D interactive animation media with a Project Based Learning approach on student learning outcomes in learning Natural and Social Sciences (IPAS) animal life cycle material in grade V of SD Negeri 143 Palembang. This study uses a quantitative research method with a Pre-Experimental Design type One Group Pretest-Posttest Design. The population in this study is all grade V students of SD Negeri 143 Palembang. The research sample was 36 students in class V.A with purposive sampling technique. Data collection techniques are carried out through tests (pretest and posttest) and documentation. Data analysis included normality tests and hypothesis tests using paired sample t-tests. The results of the study show that there is an influence of the use of 3D interactive animation media with the Project Based Learning approach on student learning outcomes. This is evidenced by an increase in the average score of student learning outcomes after being given treatment and the results of a hypothesis test that showed a significance value of less than 0.05 so that H₀ was rejected andHₐ was accepted. Thus, the use of 3D interactive animation media with the Project Based Learning approach is effective in improving student learning outcomes in learning social science of animal life cycle materials in grade V of SD Negeri 143 Palembang.